Functional Adaptability Essence of Hindu Rituals and Architectural Elements of Traditional Domestic Buildings in Kerala: Excerpt from the Vedas - Choyimanikandiyil, Kala; ., . (International Journal of Engineering and Technology, 2018)
The four knowledge texts of Hindu religion known as Vedas mainly include praises to God, daily rituals and other aspects such as Medicine, Architecture, food habits, personal duties etc.  The paper enumerates the various codified principles of food intake during various seasons and daily rituals adopted by a Hindu in ancient Kerala.  The author tries to find the importance of thermal balance of the human body that has been maintained through these codified living habits of a Hindu in Kerala which are based on the Vedas.  The paper also inevitably looks into the thermal properties of building and architectural elements described in the Vastusastra which are practised in the traditional Hindu domestic buildings in Kerala state in South India.  The paper concludes by stating that the food habits, rituals and building construction methods practised according to Hindu customs of Kerala closely link to the original Vedic texts.  Most importantly these sustainable practices were found to suit the adaptability of humans with the climate pattern of coastal Kerala towards attaining thermal comfort.
Keywords: Ayurveda; Food Habits in Kerala; Vastusastra; Traditional Houses of Kerala; Thermal Comfort